Pengaruh Game Online terhadap Komunikasi Orang Tua dan Anak: Studi Kasus SDN 104188 Medan Krio - Muhammad Raihan; Muhammad Rozan Khairi; Nabila Pebrilia Yolanda Putri; Noviyana Dila Sari Lubis; Raisha Fatiha Rizka; Nursapiah Harahap (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
With the rapid development of information and communication technology, it has become increasingly advanced in the history of human life, especially in social interaction and communication. One example is the emergence of online games which are popular with children, including students at SDN 104188 Medan Krio. The purpose of this obser-vation is to study the influence of online games on the communication relationship between parents and children at SDN 104188 Medan Krio with an age range of 6 to 9 years. Quantitative descriptive is the main approach to explore the influence of online games on communication between parents and children at SDN 104188 Medan Krio. It was found that 31.3% of parents thought that the impact of online games on children and family communication was negative, and another 25% had a very negative opinion. More than half of parents believe that after their children are addicted to online games, they rarely communicate with their children, and 21.9% of parents say there is almost no commu-nication because of game addiction. Online game addiction also affects children's learning and sleep.